Yawar Fiesta by José María Arguedas: two texts, two approaches (Revista de Crítica Literaria Latinoamericana, 2012)
Yawar Fiesta, the novel, and “Yawar (Fiesta)”, the short story, were written at a time in which Peruvian literature was seeking national authenticity. The novel outlines the complexity of the Andean world, where converging traditional and modern practices appear incompatible. On the other hand, the short story is about a local universe being affected by the transformational elements coming from the hegemonic capital, the central government, to the people in the countryside. However, the short story begins to move away from traditional indigenismo and shows a different type of indigenous person that had not previously been portrayed. The novel, which abandons the idea of the dual relationship and introduces a multiple perspective of the Andean world, presents a new type of character: the mestizo.
Keywords: Yawar Fiesta; Puquio; national narratives; mestizo; modernity; tradition